Identification of Diseases Occurring in Toddlers in the Work Area of the Lohia Health Center for the January-May 2023 period - Sartina Sartina; Yuli Sartika (Jurnal EduHealth, 2023)
This research will be conducted in June 2023 at the Lohia Health Center. The population in this study were all toddlers in the working area of ​​the Lohia Health Center, Lohia District, Muna Regency, totaling 109 toddlers at the beginning of January-May 2023. The sampling technique in this study used total sampling, namely toddlers in the work area at the Lohia Health Center, Muna Regency, totaling 109 toddlers. in early January-May 2023. Secondary data is data obtained from the working area of ​​the Lohia Health Center in the form of data on the number of diseases in toddlers. There are 4 types of diseases that are often experienced by toddlers in the Lohia Health Center Work Area, namely ISPA 72.48%, Diarrhea 8.26%, Dermatitis 13.76% and Allergies 5.5%. If reviewed based on the results obtained that diseases that often occur in toddlers in the Lohia Health Center Work Area are caused by several factors, namely environmental factors that are not clean, maternal knowledge factors about skin care in toddlers and genetic factors.